Proportional Feedback Control of Laminar Flow over a Hemisphere Using Time-Averaged Sensing Velocity at Re = 300 평균 센싱 속도를 이용한 Re=300의 반구 주위 층류 유동의 비례 되먹임 제어 - Yun, Jinhyeok; Lee, Jungil (Transactions of the Korean Society of Mechanical Engineers, B, 2023)
In this study, proportional feedback control with a time-averaged sensing velocity is applied to laminar flow over a hemisphere. Blowing/suction actuation, as a control input, is distributed on a local slot on the surface of the hemisphere before flow separation, and its strength is linearly proportional to the time-averaged transverse velocity at a sensing location on the centerline of the wake. For this purpose, we perform numerical simulations of flow over a hemisphere at Re = 300. Through a parametric study, we determine the optimal proportional gain for reducing the lift fluctuations of the hemisphere. The present control attenuates the velocity fluctuations at the sensing location and weakens the strength of the vortex structures in the wake, resulting in a reduction in the lift fluctuations of the hemisphere.
Keywords: Active control; Centerlines; Control inputs; Flow over a hemisphere; Linearly proportional; Parametric study; Proportional feedback; Proportional feedback control; Time-averaged; Transverse velocity; Active Control; Flow Control; Flow over a Hemisphere; Proportional Feedback Control